Relationship between Communication and Job Stress to Employee Job Satisfaction at Waroeng Spesial Sambal Mayjend Sutoyo Branch, Yogyakarta - Afrilla Danisa; Nurul Putrie Utami (Journal of Food and Culinary, 2023)
Communication and work stress influence job satisfaction and work productivity. Employee work productivity is an essential indicator for every company in its business activities regarding product quality and quantity. This study aims to obtain empirical evidence of the effect of communication and work stress on the job satisfaction of Waroeng Special Sambal or SS employees at the branch of Mayjend Sutoyo Yogyakarta. This type of research is an observational study with cross-sectional methods. The subjects used in this study were all Waroeng Special Sambal (SS) Mayjend Sutoyo Branch employees, totaling 33 people. The sampling technique used in this study used a purposive sampling method. The data was collected using a validated questionnaire measured by a Likert scale. Data analysis techniques used SPSS application with validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, test (R), t-test, and F test. This research was conducted from February 17, 2023, to March 19, 2023. This study showed that communication had no significant effect on employee job satisfaction. However, work stress negatively and significantly affects employee job satisfaction. Both communication and work stress influenced employee job satisfaction based on simultaneous tests. Therefore, in this study, stress significantly influences employee job satisfaction more than communication in Waroeng SS Mayjend Sutooyo Branch.